New chronological data (ESR and ESR/U‐series) for the earliest Acheulian sites of north‐western Europe. (20th November 2015) - Voinchet, Pierre; Moreno, Davinia; Bahain, Jean‐Jacques; Tissoux, Hélène; Tombret, Olivier; Falguères, Christophe; Moncel, Marie‐Hélène; Schreve, Danielle; Candy, Ian; Antoine, Pierre; Ashton, Nick; Beamish, Matt; et al.
ABSTRACT: Increasing evidence suggests that bifacial technology (Acheulian, Mode 2) arrived in Europe during the early Middle Pleistocene, i.e. significantly earlier than previously proposed. In northern France and Britain, much of the age attribution for these assemblages has been based on biostratigraphy and lithostratigraphy rather than absolute dates. This study presents a systematic application of electron spin resonance (ESR) dating of sedimentary quartz and ESR/U‐series dating of fossil tooth enamel to key Acheulian sites of this area. Although the age estimates have large associated uncertainties, most of the derived dates are consistent with existing age estimates. The new chronologies and the problems associated with dating material of early Middle Pleistocene age are discussed. In Britain, the earliest archaeology (cores and flakes, Mode 1) is older than Marine Isotope Stage (MIS) 15, whereas localities containing Acheulian technologies span late MIS 15/MIS 13 through to MIS 9. A similar pattern is seen in northern France although age estimates from sites such as la Noira suggest the possible appearance of the Acheulian in central France as early as MIS 17. The dates presented here support the suggestion that the earliest Acheulian appeared in NW Europe during the early Middle Pleistocene, significantly after its appearance in the southern parts of the continent.